If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3b+2)-7=9
We simplify the equation to the form, which is simple to understand
2(3b+2)-7=9
Reorder the terms in parentheses
+(+6b+4)-7=9
Remove unnecessary parentheses
+6b+4-7=+9
We move all terms containing b to the left and all other terms to the right.
+6b=+9-4+7
We simplify left and right side of the equation.
+6b=+12
We divide both sides of the equation by 6 to get b.
b=2
| 13-4/2x=37 | | x^2+13x+65=0 | | 4=2(x+3) | | 4(n-2)= | | 0=8z-(3-2) | | 3r+22= | | x+10/3=4 | | X-7(x+4)=68 | | 2+2x-3=2x-4+3x-1 | | -6n-2n=15 | | 0.3t+0.18(5000-t)=0.21(5000) | | x(8x+19)=3x^2-14x+56 | | y-55=9x-45 | | 4x+16=80 | | -5y+12=4(2y+3) | | -0.312-2.4x=0.9(2.5x+1.1) | | 2n+n+-3=9 | | 6x-2=x-7 | | (3/5(25/9))-(2/3) | | (2x-1)(4+5x)=0 | | 3/2a=75 | | 3x-21=2x-21 | | x+(1/4)x=(7/8) | | 3(2x-1)-2=13 | | 302-2a=210 | | 3/4m-5-1/2m | | 2-1/2=x | | m+4-4m+3= | | (x+2.1)-(0.1x+3)=11 | | x-10403=116 | | 5b=3.55 | | -22+6x=44-5x |